2015
DOI: 10.1371/journal.pone.0116622
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of an Internet Intervention for Family Caregivers of People with Dementia: Results of a Randomized Controlled Trial

Abstract: BackgroundThe World Health Organization stresses the importance of accessible and (cost)effective caregiver support, given the expected increase in the number of people with dementia and the detrimental impact on the mental health of family caregivers.MethodsThis study assessed the effectiveness of the Internet intervention ‘Mastery over Dementia’. In a RCT, 251 caregivers, of whom six were lost at baseline, were randomly assigned to two groups. Caregivers in the experimental group (N = 149) were compared to c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
222
0
3

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 178 publications
(237 citation statements)
references
References 35 publications
5
222
0
3
Order By: Relevance
“…org/education/e-learning/), and patient organizations (http://www.scie.org.uk/dementia/ e-learning/). Few internet-delivered e-learning programs for informal dementia carers have been evaluated in randomized controlled trials, demonstrating benefits regarding caregiver empathy (Hattink et al, 2015), depression and anxiety (Blom et al, 2015), and perceived stress (Kajiyama et al, 2013). It is not clear to date whether this type of intervention can increase behavior management skills, alleviate psychological and interpersonal problems, enhance help-seeking competence, or improve self-care.…”
Section: Discussionmentioning
confidence: 99%
“…org/education/e-learning/), and patient organizations (http://www.scie.org.uk/dementia/ e-learning/). Few internet-delivered e-learning programs for informal dementia carers have been evaluated in randomized controlled trials, demonstrating benefits regarding caregiver empathy (Hattink et al, 2015), depression and anxiety (Blom et al, 2015), and perceived stress (Kajiyama et al, 2013). It is not clear to date whether this type of intervention can increase behavior management skills, alleviate psychological and interpersonal problems, enhance help-seeking competence, or improve self-care.…”
Section: Discussionmentioning
confidence: 99%
“…The number of high quality trials evaluating a multi-component intervention for family carers of people with dementia continues to increase (Blom et al, 2015;Livingston et al, 2014) and it is interesting to compare our findings with the results of these recent trials in terms of the composition and delivery of the intervention being evaluated. In one RCT, where the intervention group showed significantly lower depressive symptoms and anxiety (Blom et al, 2015), the internet delivered intervention, Mastery over Dementia, developed from the results of systematic reviews (Pinquart and Sorensen, 2006) and with active carer participation via activities, comprised the key components we found most effective: education (on dementia and carer coping skills); CBT (cognitive reframing) and guidance on increasing social support (Blom et al, 2015). In contrast, a RCT of a multicomponent dyadic intervention (education, exercise and social activities) delivered by home visits but lacking the psychological component of cognitive reframing, revealed no significant benefits in any of the carer outcomes (Prick et al, 2015).…”
Section: Implications For Future Research and Practicementioning
confidence: 93%
“…Nature of the intervention Seven reviews reported on studies of technology-based interventions; six were of moderate quality (Boots et al, 2014;Elvish et al, 2013;Olazaran et al, 2010;Peacock and Forbes, 2003;Pusey and Richards, 2001;Thompson et al, 2007) and one was high quality (Lins et al, 2014). Reviews varied considerably in the degree of definition of the intervention; 2 reviews did not specify any definition (Peacock and Forbes, 2003;Pusey and Richards, 2001).…”
Section: Technology-based Interventionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although this may be a seductive option to consider, this type of dosage might be helpful for some clinical presentations, but would probably not be enough for sustained changes in behavioural symptoms, and associated distress in those with clinically significant CB. For example, a recent internet-based dementia support solution has been applied in family settings with good outcomes on some aspects of carer well-being, 351 but the authors do not report any impact on their measures of behavioural symptoms.…”
Section: Overview Of Key Findings From Challenge Demcarementioning
confidence: 99%